2020
DOI: 10.31234/osf.io/z6pcg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The growth and form of knowledge networks by kinesthetic curiosity

Abstract: Throughout life, we might seek a calling, companions, skills, entertainment, truth, self-knowledge, beauty, and edification. The practice of curiosity can be viewed as an extended and open-ended search for valuable information with hidden identity and location in a complex space of interconnected information. Despite its importance, curiosity has been challenging to computationally model because the practice of curiosity often flourishes without specific goals, external reward, or immediate feedback. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…It is that these prior divisions parcel out the idea too soon. Philosophy and psychology consider whether curiosity is internal or external, perceptual versus epistemic, or specific versus diversive, or kinesthetic ( Kidd and Hayden, 2015 ; Berlyne, 1950 ; Zhou et al, 2020 ). Computer science tends to define it as needed, for the task at hand ( Stanley and Miikkulainen, 2004b ; Friston et al, 2016 ; Lehman and Stanley, 2011b ; Lehman et al, 2013 ; Mouret and Clune, 2015 ; Colas et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is that these prior divisions parcel out the idea too soon. Philosophy and psychology consider whether curiosity is internal or external, perceptual versus epistemic, or specific versus diversive, or kinesthetic ( Kidd and Hayden, 2015 ; Berlyne, 1950 ; Zhou et al, 2020 ). Computer science tends to define it as needed, for the task at hand ( Stanley and Miikkulainen, 2004b ; Friston et al, 2016 ; Lehman and Stanley, 2011b ; Lehman et al, 2013 ; Mouret and Clune, 2015 ; Colas et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…We made an idealistic choice that worked out. The field of curiosity studies has shown that there are many kinds of curiosity (79, 23, 25, 27, 28, 30, 33, 34, 39, 47, 80, 94, 95). At the extreme limit of this diversity is a notion of curiosity defined for any kind of observation, and any kind of learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, preferring familiarity can manifest as a form of perseverative information seeking that was associated with deprivation curiosity (Lydon-Staley, , a drive to reduce uncertainty and acquire missing information (Kashdan et al, 2018;. This preference for familiarity has been seen as prevalent in people with greater depressed mood and anxiety (Zhou et al, 2023), and may be an important heuristic strategy to reduce uncertainty for better reliability of future-oriented decisions (Harhen & Bornstein, 2023;Jiang, Kulesza, Singh, & Lewis, 2015). However, in large environments, such local heuristics are impoverished, particularly when higher-order associations are needed for planning.…”
Section: Introductionmentioning
confidence: 99%
“…In the second case, the main focus is instead on the network of existing relations between different items [23]. Hence, the modeling attention is shifted towards the cognitive processes through which single individuals explore the space of different possibilities and produce sequences of explored items in search of novelties [24][25][26]. In this latter way of interpreting adoption dynamics, different exploration (and innovation) models have been proposed to replicate the process of exploration according to which one idea, concept or item leads to another, and a discovery can trigger further ones [27,28].…”
Section: Introductionmentioning
confidence: 99%